The Crop Insurance Systems in Poland Towards the EU - Agnieszka Parlińska; Maria Parlińska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The increasing number of unfavorable conditions of agricultural production causes the farmers to suffer severe losses in their activity. At the same time, the increase in the profitability of agricultural production, the support of numerous European Union funds, led to increased interest in insurance as an instrument supporting agricultural risk management. Hence, both the agricultural industry and the insurance industry see the need to create an effective agricultural and livestock insurance system. The paper examines the changes and scope of crop insurance in Poland towards the European Countries. There were presented issues connecting to policies, regulation and state aid rules, crop insurance level in EU countries and characteristic of the crop insurance market – case study Poland. There was used descriptive and comparative methods, as well as the selected statistical method. The analysis was performed in the years 2005-2016.